The Comprehensive Systematic Review of Association of Non-Nutritive Sweetener Consumption to Potential Effects of Glucose Intolerance - Devina Adelina Wijaya; Clareta Vero Patricia Widya (International Medical Journal Corp. Ltd, 2026)
Introduction: Non-nutritive sweeteners (NNS) are widely used as sugar substitutes to reduce caloric intake and manage body weight, yet their long-term metabolic effects, particularly on glucose tolerance, remain controversial. While acute studies often report neutral effects, emerging evidence suggests that chronic consumption, especially of certain NNS types, may adversely affect insulin sensitivity and glucose homeostasis in specific populations (Romo-Romo et al., 2018; Suez et al., 2022). Methods: A comprehensive systematic review was conducted, screening studies based on predefined inclusion criteria: human participants, NNS exposure assessment, glucose metabolism outcomes, appropriate study designs (RCTs, cohort studies, systematic reviews), and methodological quality. Data extraction covered NNS type, dosage, study population, glucose outcomes, study design, key findings, and proposed mechanisms. A total of 80 studies were included and critically synthesized. Results: The evidence reveals significant heterogeneity in NNS effects. Acute NNS exposure generally has minimal impact on postprandial glucose and insulin (Greyling et al., 2020), but chronic consumption (≥2 weeks), particularly of sucralose, is associated with decreased insulin sensitivity in healthy, lean, non-habitual users (Romo-Romo et al., 2018, 2024, 2025). Effects vary by sweetener type: stevia shows neutral to beneficial effects on fasting glucose (Bai et al., 2024; Zare et al., 2024), aspartame largely exhibits neutral metabolic impact (Santos et al., 2018; Higgins et al., 2018), while saccharin and sucralose demonstrate more variable, often microbiome-dependent outcomes (Suez et al., 2022; Méndez-García et al., 2022). Population characteristics, including baseline metabolic health and habitual NNS use, significantly moderate these effects. Discussion: The divergence in findings can be explained by population-specific responses, sweetener-specific mechanisms (e.g., gut microbiota modulation by sucralose), study duration, methodological quality, and comparator substances. When NNS replace sugar-sweetened beverages, they generally offer a net metabolic benefit, supporting their role in dietary strategies for sugar reduction (McGlynn et al., 2020; Lee et al., 2022). Conclusion: The impact of NNS on glucose metabolism is not uniform but is influenced by sweetener type, consumption duration, and individual host factors such as metabolic health and gut microbiome composition. While certain NNS may pose risks to insulin sensitivity in metabolically naive individuals, they remain a preferable alternative to caloric sweeteners for weight and glycemic management in broader populations. Future research should focus on personalized nutrition approaches and long-term outcomes.